(untitled) (Biological Sciences - PJSIR, 1996)
After having established proper analytical methodology for multiple pesticide residues, major cotton growing areas of Pakistan were surveyed extensively and 250 samples of cotton seeds were drawn from progressive farmers’ fields and different ginning factories during three crop seasons (June, 1986-January, 1989). Laboratory investigation of these samples showed contamination in 73.6 % samples with 24 different pesticides/metabolites. The results indi- cated that out of 24 pesticides, 9 were organochlorine, 8 organophosphorus and 7 synthetic pyrethroid compounds. MRLs exceeded in 40.6% samples. The most frequently occuring pesticides were cyhalothrin, dimethoate, DDT and its metabolites, endosulfan and monocrotophos.